Fast and deep disinfection for face masks recycle using vacuum ultraviolet irradiation. (25th September 2022) - Ye, Shengjun; Li, Yiheng; Huang, Haibao; Xu, Yanbin; Du, Shaoping; Wan, Fenlong; Xie, Ruijie; Huang, Pingli; Liu, Biyuan; Dong, Tao; He, Zhili; Leung, Dennis Y.C.
Abstract: Nowadays, trillions of used face masks have caused serious environmental pollution, biological risk and energy waste due to improper disposal. It is highly necessary to disinfect and recycle the used masks. In this paper, a sustainable vacuum ultraviolet (VUV) treatment for disinfection of N95 masks was first studied. Typical antibiotic-resistant E. coli were completely inactivated with decreased abundances by 65.82% for 16S rRNA and 76.75% for SHV-4 (an antibiotic-resistance gene) in 5 min, which was further decreased by more than 90% after the prolonged treatment. The mechanism was demonstrated that VUV could damage the exterior structure and interior DNA of E. coli cells due to the synergy of UV, O3 and extensive reactive oxygen species (ROS). The treated N95 masks had no structural damage and functional decline, and were up to the reuse standard. Moreover, a VUV disinfection equipment was fabricated, which can inactivate E. coli cells on the face masks in a few seconds and keep the used masks intact after 20 cycles of disinfection. This study provides a fast, deep and economical disinfection strategy for masks recycling, which can effectively reduce the consumption of fossil energy and plastic pollution to maintain sustainable development. Graphical abstract: Image 1 Highlights: The ESBL- E.coli and its ARGs on face masks were deeply destroyed by VUV irradiation. O3, UV254 and ROS are involved in the deep inactivation of E.coli in VUV system. An applied VUV equipment was fabricated for efficient face masks disinfection. Treated masks are undamaged and can be re-worn after the VUV treatment.